The prevalence of Healthcare Effectiveness Data and Information Set (HEDIS) initiation and engagement in treatment among patients with cannabis use disorders in 7 US health systems. Issue 3 (3rd July 2019) - Lapham, Gwen T.; Campbell, Cynthia I.; Yarborough, Bobbi Jo H.; Hechter, Rulin C.; Ahmedani, Brian K.; Haller, Irina V.; Kline-Simon, Andrea H.; Satre, Derek D.; Loree, Amy M.; Weisner, Constance; Binswanger, Ingrid A.
Abstract: Background: Cannabis use disorders (CUDs) have increased with more individuals using cannabis, yet few receive treatment. Health systems have adopted the Healthcare Effectiveness Data and Information Set (HEDIS) quality measures of initiation and engagement in alcohol and other drug (AOD) dependence treatment, but little is known about the performance of these among patients with CUDs. Methods: This cohort study utilized electronic health records and claims data from 7 health care systems to identify patients with documentation of a new index CUD diagnosis (no AOD diagnosis ≤60 days prior) from International Classification of Diseases, Ninth revision, codes (October 1, 2014, to August 31, 2015). The adjusted prevalence of each outcome (initiation, engagement, and a composite of both) was estimated from generalized linear regression models, across index identification settings (inpatient, emergency department, primary care, addiction treatment, and mental health/psychiatry), AOD comorbidity (patients with CUD only and CUD plus other AOD diagnoses), and patient characteristics. Results: Among 15, 202 patients with an index CUD diagnosis, 30.0% (95% confidence interval [CI]: 29.2–30.7%) initiated, 6.9% (95% CI: 6.2–7.7%) engaged among initiated, and 2.1% (95% CI: 1.9–2.3%) overall both initiated and engaged in treatment. The adjusted prevalence of outcomes varied across index identification settings and was highest among patients diagnosed in addiction treatment, with 25.0% (95% CI: 22.5–27.6%) initiated, 40.9% (95% CI: 34.8–47.0%) engaged, and 12.5% (95% CI: 10.0–15.1%) initiated and engaged. The adjusted prevalence of each outcome was generally highest among patients with CUD plus other AOD diagnosis at index diagnosis compared with those with CUD only, overall and across index identification settings, and was lowest among uninsured and older patients. Conclusion: Among patients with a new CUD diagnosis, the proportion meeting HEDIS criteria for initiation and/or engagement in AOD treatment was low and demonstrated variation across index diagnosis settings, AOD comorbidity, and patient characteristics, pointing to opportunities for improvement.